Pengembangan Permainan Untuk Pembelajaran Angka Dan Huruf Hijaiyah Berbasis Android - Andhika Hanifa Naufaliawan; R. Rizal Isnanto; Ike Pertiwi Windasari (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2015)
The development of increasingly advanced technology has a vital role in all sectors of management, which includes the processing of data. Moreover, with the development of the internet is so fast these days that requires every person to obtain information quickly and accurately. Associated with it then there is a game that has grown rapidly with variations of each preparation This application uses the software Construct 2 as editor. Multimedia Development Life Cycle used as methodology for developing this game. Stages of research method, namely literature, game design, game implementation, testing, and analysis. User applications can execute all the menus contained in the application “Belajar Angka dan Huruf Hijaiyah”. With this application android-based user can exercise anytime and anywhere, and this application can run well when tested using black-box and got positive results when tested to application user.